SG-APSIC1107: Surgical-site infection in Hung Vuong Hospital, a gynecology and obstetrics tertiary-care hospital in Ho Chi Minh City, Vietnam - Anh Dinh; Phan Thi Hang; To Gia Kien; Tran Thi Thuy Hang; Ngo My Nhung; Ngo Thi Thanh Tham (Cambridge University Press, 2023)
Objectives: Surgical site infection (SSI) is the most common healthcare-associated infection (HAI) in our gynecology and obstetrics hospital. SSI among patients following gynecological and obstetrical surgery not only results in increased morbidity but also has far-reaching implications. Thus, this study was conducted to determine the incidence, risk factors, and bacterial pathogens related to SSI. Methods: We conducted this retrospective study based on medical records from January 2019 to December 2020 at Hung Vuong Hospital. Results: Of 51,466 patients undergoing surgery, 581 patients (1.34%) developed an SSI after cesarean section and 145 patients (1.77%) developed an SSI after gynecological surgery. A multivariate logistic regression analysis identified the following risk factors among patients who underwent cesarean section: age (OR, 1.02; 95% CI, 1.01-1.04), emergency cesarean section (OR, 1.62; 95% CI, 1.36-1.93), operation time >60 minutes (OR, 2.04; 95% CI, 1.48-2.80), surgery during the night shift (OR, 1.29; 95% CI, 1.08-1.54), and prolonged hospital stay ≥2 days (OR, 1.51; 95% CI, 1.21-1.89). SSI risk factors for patients following gynecological surgery included age (OR, 1.03; 95% CI, 1.02-1.05), contaminated wound (OR, 3.44; 95% CI, 1.56-7.57), dirty wound (OR, 3.61; 95% CI, 1.44-9.05), vertical abdominal incision (OR, 2.49; 95% CI, 1.65-3.77), and duration of surgery >180 minutes (OR, 2.02; 95% CI, 1.24-3.29). Staphylococcus aureus was the most commonly identified SSI pathogen following cesarean section (49.56%), and Escherichia coli was isolated in 44.93% of SSIs among patients undergoing gynecological surgery. Conclusions: SSI interventions should target this high-risk group. Based on microbiology culture and susceptibility results isolated from SSI cases, novel antibiotic therapies are needed to treat SSIs.